2022
DOI: 10.1002/iid3.648
|View full text |Cite
|
Sign up to set email alerts
|

Reduced cutaneous CD200:CD200R1 signaling in psoriasis enhances neutrophil recruitment to skin

Abstract: Introduction The skin immune system is tightly regulated to prevent inappropriate inflammation in response to harmless environmental substances. This regulation is actively maintained by mechanisms including cytokines and cell surface receptors and its loss results in inflammatory disease. In the case of psoriasis, inappropriate immune activation leads to IL‐17‐driven chronic inflammation, but molecular mechanisms underlying this loss of regulation are not well understood. Immunoglobulin family me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…As we 17 and others 18 have demonstrated reduced CD200 levels in samples from patients with psoriasis and CD200R1 signaling has been shown to dampen immune responses, 7 , 8 , 9 , 10 , 11 , 12 , 13 we hypothesized that the absence of CD200R1 would enhance inflammation in psoriasis models. Contrary to this, global CD200R1 deficiency protected mice from skin thickening in a model induced by repeated intradermal injection with IL-23 19 ( Figs.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…As we 17 and others 18 have demonstrated reduced CD200 levels in samples from patients with psoriasis and CD200R1 signaling has been shown to dampen immune responses, 7 , 8 , 9 , 10 , 11 , 12 , 13 we hypothesized that the absence of CD200R1 would enhance inflammation in psoriasis models. Contrary to this, global CD200R1 deficiency protected mice from skin thickening in a model induced by repeated intradermal injection with IL-23 19 ( Figs.…”
Section: Resultsmentioning
confidence: 95%
“…We have previously shown that the ligand CD200 is reduced in nonlesional psoriatic skin 17 and we therefore hypothesized that in healthy skin, CD200R1 signaling prevents inappropriate inflammation; however, in psoriasis, this is reduced, contributing to psoriasis susceptibility. To examine this hypothesis, here, we compare the severity of inflammation in psoriasis models in wild-type (WT) and CD200R1-deficient mice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, diagnosis of PsO mainly depends on the assessment of medical history and clinical signs by trained dermatologists, which requires the collaboration of a specialized and trained dermatologist, laboratory technician, and dermatopathologist. To better diagnose and treat PsO, a wide range of biomarkers and targets have been investigated 10–12 . Inflammatory‐related mediators such as IL‐17A, IL23A, and TNF‐α have been reported to be important biomarkers for disease activity of PsO 2,10 .…”
Section: Introductionmentioning
confidence: 99%
“…To better diagnose and treat PsO, a wide range of biomarkers and targets have been investigated. [10][11][12] Inflammatory-related mediators such as IL-17A, IL23A, and TNF-α have been reported to be important biomarkers for disease activity of PsO. 2,10 Based on the pathological process of PsO, targeting related signaling pathways and molecules can be an effective way to develop therapeutic drugs.…”
Section: Introductionmentioning
confidence: 99%